Down-regulatory mechanism of mammea E/BB from Mammea siamensis seed extract on Wilms' Tumor 1 expression in K562 cells - Rungrojsakul M. (2017)
© 2016 Rungrojsakul et al. Background: Wilms' tumor 1 (WT1) is a biological marker for predicting leukemia progression. In this study, mammea E/BB, an active compou nd from Saraphi (Mammea siamensis) seed extract was examined for its effect on down-regulatory mechanism of WT1 gene expression, WT1 protein and mRNA stability, and cell proliferation in K562 cell line. Methods: M. siamensis seeds were obtained from the region of Chiang Mai (North of Thailand). Mammea E/BB was extracted from seeds of M. siamensis. WT1 protein expression and stability were evaluated by Western blot analysis. WT1 mRNA stability was assessed by qRT-PCR. WT1-DNA binding and WT1 promoter activity were assayed by ChIP assay and luciferase-reporter assay, respectively. Cell cycle arrest was studied by flow cytometry. Results: Treatment with mammea E/BB led to down-regulation of WT1 expression. The suppression of WT1 expression did not involve protein and mRNA degradation. Rather, WT1 protein was down-regulated through disruption of transcriptional auto-regulation of the WT1 gene. Mammea E/BB inhibited WT1-DNA binding at the WT1 promoter and decreased luciferase activity. It also disrupted c-Fos/AP-1 binding to the WT1 promoter via ERK1/2 signaling pathway and induced S phase cell cycle arrest in K562 cells. Conclusion: Mammea E/BB had pleotropic effects on kinase signaling pathways, resulting in inhibition of leukemia cell proliferation.